Coping with COVID-19: Ehich resilience mechanisms enabled Austrian nonprofit organizations to weather the pandemic storm? - Sandra Stötzer; Katharina Anna Kaltenbrunner; Birgit Grüb; Sebastian Martin (Schmalenbach Journal of Business Research (SBUR), 2022)
The ongoing COVID-19 pandemic triggered a global crisis affecting the work and partially the existence of businesses, governments, administrations and nonprofit organizations (NPOs). The latter not only faced severe challenges themselves, but also play(ed) a major role in fighting the pandemic, especially those offering services in social and health care. Maintaining service delivery under pandemic conditions to serve the often vital needs of clients requires (organizational) resilience. This concept generally relates to the ability to withstand adversity, to adapt in a turbulent environment and respond to (disruptive) change. Based on a qualitative content analysis of 33 interviews with nonprofit executives, this paper explores the impact of the pandemic on Austrian NPOs active in health and social care in terms of contextual challenges faced. Our study contributes to (nonprofit) resilience research and extreme context research literature as it illustrates how NPOs coped with this disruptive extreme context. Our findings show which resilience mechanisms (i.e. all kinds of resilient behavior, resources and capabilities) were helpful in overcoming pandemic challenges and getting through these hard times.
Keywords: 650; COVID-19 pandemic; Extreme context research; Nonprofit organizations; Pandemic challenges; Resilience mechanisms; Social and health care